HUBUNGAN POLA ASUH PEMENUHAN NUTRISI DENGAN STATUS GIZI BALITA - Resi Putri Naulia; Farhan Nafis Sajidalloh (Indonesian Journal of Nursing Scientific, 2025)
Parenting patterns are a very influential factor in child development, especially in the aspect of early childhood nutritional growth and development. Ineffective nutrition parenting in family may caused under- five year childrean malnourished. This study aimed to determine the correlation of parenting nutrition with nutritional status of toddlers. A cross-sectional design applied to 80 mothers who have children aged 0-59 months. The data collection tool used a questionnaire, the nutritional status of toddlers was measured by weight/height indicators. Data analysis used chi-square. The results of the study showed that there were significant associations between nutrition parenting and the nutritional status of toddlers (p < 0.026). From this study, parents are expected to be able to apply appropriate nutritional parenting patterns to their children so that their development runs normally according to their age.